2021
DOI: 10.25259/ijdvl_565_20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of 0.5% timolol solution in the treatment of pyogenic granuloma: A randomized, double-blind and placebo-controlled study

Abstract: Introduction: Pyogenic granulomas are benign vascular lesions of the skin and mucosa which are often a source of concern because of their recurrent bleeding even with minimal trauma. Current treatment for pyogenic granuloma is ablative; no medical therapy is standardized to date. Timolol, due to its vasoconstrictive effect, vascular growth factor inhibition and apoptosis promotion properties, is a potential therapeutic option. Objectives: To assess the effectiveness and safety of topical timolol in the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Topical corticosteroids affect the pathogenesis of PG in several ways, including vasoconstriction and inhibiting proangiogenic agents. β-blockers effectiveness was reported in terms of solitary PG lesions regression [ 12 ]. Although β-blockers have a gradual effect in treating PGs and the period of treatment would take more than 6 weeks, it can avoid the adverse effects of other treatments including scar formation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical corticosteroids affect the pathogenesis of PG in several ways, including vasoconstriction and inhibiting proangiogenic agents. β-blockers effectiveness was reported in terms of solitary PG lesions regression [ 12 ]. Although β-blockers have a gradual effect in treating PGs and the period of treatment would take more than 6 weeks, it can avoid the adverse effects of other treatments including scar formation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical excision is the first-line treatment [ 1 ], many PG cases regress spontaneously upon follow-up only, with mild chances of scars formation [ 11 ]. Therefore, recent studies suggested a 6 weeks follow-up protocol alongside the appliance of topical β-blockers [ 12 ]. A recent review also suggested topical steroids and timolol as an efficient treatment, especially in cases of young ages and sites of cosmetic issues [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We thank the readers of our article 1 for going through it in detail and for including it in a journal club discussion. 2 The primary conclusions of our study were:…”
Section: Sirmentioning
confidence: 99%
“…6 Barry et al 6 early PG with a greater vascular component. 7 Some authors suggest that small PGs (<4 mm) may also respond favorably to the topical therapy. 6 However, according to Patra et al, 7 the percentage reduction in size showed no correlation with baseline size of the lesion and duration of the lesion.…”
Section: A Case Of Multiple Pyogenic Granulomas Of the Trunk Successf...mentioning
confidence: 99%